2011
DOI: 10.1002/lary.21290
|View full text |Cite
|
Sign up to set email alerts
|

Electromyographic and histologic evolution of the recurrent laryngeal nerve from transection and anastomosis to mature reinnervation

Abstract: Consistent EMG, histologic, and vocal fold motion changes occur at specific time periods during RLN reinnervation after transection and anastomosis in a rat model. Reinnervation is mature at 16 weeks. Findings corroborate theories of preferential and synkinetic reinnervation after RLN transection. Use of a rat model to investigate the effect of interventions on RLN reinnervation requires a minimum of 16 weeks between transection and investigation to allow for maturation of reinnervation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 22 publications
4
45
0
Order By: Relevance
“…For the early group, optimal fitting of the time to recovery yielded a mean of 4.2 weeks and standard deviation of 1.4 weeks. It follows that 95% of the early group should recover within about 6 to 7 weeks, which is consistent with studies of synkinesis in a rat model . In a systematic review of idiopathic vocal fold paralysis, five cases out of 717 (0.7%) recovered beyond a year, which is consistent with the model prediction of approximately 1% recovering beyond 12 months.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…For the early group, optimal fitting of the time to recovery yielded a mean of 4.2 weeks and standard deviation of 1.4 weeks. It follows that 95% of the early group should recover within about 6 to 7 weeks, which is consistent with studies of synkinesis in a rat model . In a systematic review of idiopathic vocal fold paralysis, five cases out of 717 (0.7%) recovered beyond a year, which is consistent with the model prediction of approximately 1% recovering beyond 12 months.…”
Section: Discussionsupporting
confidence: 82%
“…It follows that 95% of the early group should recover within about 6 to 7 weeks, which is consistent with studies of synkinesis in a rat model. 23 In a systematic review of idiopathic vocal fold paralysis, 2 five cases out of 717 (0.7%) recovered beyond a year, which is consistent with the model prediction of approximately 1% recovering beyond 12 months. Rather than regarding these delayed recoverers as anomalies, they are simply the tail part of the same probability distribution describing the entire population of recoverers.…”
Section: Predictions Of the Model Are Consistent With Published Datasupporting
confidence: 67%
“…Reinnervation after freezing injury induced an increased number of myelinated axons with smaller diameter, as already reported . Considering that axon diameter and degree of myelination depend on the axon maturation, the axonal growth rate seems lower than in other studies where the RLn morphologic appearance was comparable to control nerve 20 weeks after injury . Rate of reinnervation is determined by many factors like species, age, type of nerves, nature of injury, and distance from target organ and neuronal cell body .…”
Section: Discussionmentioning
confidence: 81%
“…This recovery is delayed up to 16 wpi when the injury is a transection and anastomosis (Pitman et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…A functional score was assigned to the left vocal fold movements observed, with a score of 0 being assigned to a paralyzed vocal fold; 1 for a slight movement being visible; 2 for normal or near to normal movement. Work by previous authors has shown that the effects of the anesthetic used upon laryngeal fold mobility appear to be minimal (Aoyama et al 2010;Pitman et al 2011).…”
Section: Functional Evaluationmentioning
confidence: 99%